Factor Analysis of Service Quality, Price Perception, and Brand Image on Word of Mouth mediated by Satisfaction Variables at Poundfit Rocca Space Jakarta - Naifahrani Balqis Hutama; Afriapollo Syafaruddin (International Journal of Management Science and Application, 2023)
Rocca Space as a sports community that has not been established for too long, Rocca Space wants its brand to be recognized by the wider community in Jakarta to all regions in Indonesia. The form of effort made is to test and analyze in terms of service quality, price perception, brand image, and customer satisfaction that can create positive word of mouth from individuals to other individuals. This study aims to determine, test, and analyze the relationship between word of mouth variables, with independent variables, service quality, price perception, brand image, and customer satisfaction as mediating variables, resulting in research implications. This study uses a descriptive research type method with a quantitative approach. The population of this study were Pound Fit Rocca Space Jakarta customers, with a minimum sample size of 145 respondents. The data processing carried out in this study was SmartPLS. The results of this study indicate that service quality, price perception, brand image, and customer satisfaction have a significant effect on word of mouth. Customer satisfaction does not affect the relationship between price perception and word of mouth. Price perception also has no significant effect on customer satisfaction. The contribution of this research can develop the repertoire of management science, especially in the field of marketing management. Namely related to discussing research on service quality, price perception, brand image, satisfaction, and word of mouth so that the theoretical studies in this study can be used by future researchers and can be developed again on other variables such as brand awareness, brand trust, and reputation.